Experimental study on performance improvement of anionic surfactant foaming agent by xanthan gum. (10th January 2020) - Zhu, Han; Chen, Longlong; Xu, Jie; Han, Qinghua
Highlights: Xanthan gum was used as a foam stabilizer for anionic surfactant foaming agent. The surface tension of the foaming liquid was tested by the drop weight method. Optical microscopy was used to analyse the microstructure of fresh foam. Abstract: The stability of foam plays a vital role in the quality of foamed concrete. In this paper, foamed concrete with dry density of 600 kg/m 3 and water-cement ratio of 0.5 had been fabricated by a commercially available anionic surfactant foaming agent with the xanthan gum as a foam stabilizer. Some essential tests were performed, like the surface tension, the foaming multiple, the bleeding rate, the compressive strength, and the water absorption test. In addition, the microstructure of fresh foam and the pore size distribution of the foamed concrete were analysed through optical microscope and scanning electron microscope (SEM), respectively.